(untitled) (Journal of Management and Social Sciences, 2024)
North-western Nigeria faces significant vulnerability to the impact of climate change. In recent years, States that comprise the zone had increasingly experienced conflicts, such as farmers-herders clashes, cattle rustling, and rural banditry, a situation aggravated by the interaction of multiple factors related to the scarcity of natural resources such as loss of grazing lands, water scarcity, erosion, and drought-induced by the climatic changing condition. This paper, therefore, explored the intersection between climate change and cattle rustling in the North-Western part of the country. The paper argued that changing in climate influenced cattle rustling and rural banditry in the North-west. Employing a qualitative approach, this paper relies on secondary data and utilises descriptive content analysis as method of data analysis to provide an insight on climate change linkage with cattle rustling as an old and emerging organized crime in the North-Western part of the country.